The recursive formula for the sequence -16, -33, -50, -67, .... is f(n) = f(n - 1) - 17, f(1) = -16
Finding the recursive formula for the sequence
From the question, we have the following parameters that can be used in our computation:
-16, -33, -50, -67, ....
In the above sequence, we can see that -17 is added to the previous term to get the new term
This means that
First term, a = -16
Common difference, d = -17
The recursive formula for the sequence is then represented as
f(n) = f(n - 1) - 17, f(1) = -16